The Old Man in Purgatory: The Indian Part in Yeats's Vision of Salvation. (October 2017) - Im, Yeeyon
Abstract : This essay examines Yeats's Purgatory via A Vision, in an attempt to understand his view of salvation in particular relation to Indian philosophy. Read from a Christian perspective, Purgatory may be a work far from purgation, as T. S. Eliot once complained. I wish to show in this essay that Purgatory indeed places emphasis on purgation by a negative example, if in a different way from the Catholic one. Yeats denies the linear eschatology of Christian theology as well as its doctrine of salvation in eternal heaven. In A Vision, Yeats explains his view of the afterlife of the soul, which involves purgation through 'the Dreaming Back'. The special treatment of the Old Man renders Purgatory a meta-purgatorial play that mirrors the Dreaming Back of his mother's spirit in the Old Man's, intensifying the theme of purgation. Purgatory effectively dramatizes the inability to forgive and cast out remorse: the impossibility of nishikam karma, or selfless action, to borrow Sanskrit terms, which is essential for Yeatsian salvation. Finally, I would also emphasize Yeats's deviation from the Hindu wisdom, which makes Yeats's vision uniquely his own.